Endoscopic ultrasound-guided entero-colostomy with lumen-apposing metal stent as a rescue treatment for malignant intestinal occlusion: a multicenter study - Neri, Benedetto; Stigliano, Serena; Biasutto, Dario; Citterio, Nicolò; Lisotti, Andrea; Fusaroli, Pietro; Mangiavillano, Benedetto; Donatelli, Gianfranco; Tonini, Giuseppe; Di Matteo, Francesco Maria (Endoscopy, 2024)
Background Surgery is the first-choice treatment for malignant intestinal obstruction (MIO); however, many patients are deemed unfit for surgery. Endoscopic ultrasound-guided entero-colostomy (EUS-EC) with a lumen-apposing metal stent (LAMS) could represent a new treatment option.Methods Consecutive patients undergoing EUS-EC for MIO from November 2021 to September 2023 at four European tertiary referral centers were retrospectively enrolled. Multidisciplinary meetings determined whether patients were unsuitable for surgery or colonic stent placement, or refused surgery. The primary outcome was technical success of EUS-EC and secondary outcomes were clinical outcome, safety, and hospital stay.Results 12 patients were enrolled (median age 72.5 [range 42–85] years; 58.3% female). Colonic adenocarcinoma was the primary tumor in 75.0% of patients and 91.7% had stage IV disease. Technical success was 100%. No LAMS misdeployment or other procedural adverse events occurred; three patients (25.0%) had severe post-procedural complications. Clinical success was achieved in 10 patients (83.3%), with 5 (50.0%) resuming chemotherapy after the procedure. Median post-procedural hospital stay was 9 (1–20) days and median overall survival was 47.5 (2–270) days.Conclusions EUS-EC was a feasible technique and could be considered a possible alternative to standard approaches for MIO in highly selected patients.